Unconscionability - statutory prevention of unethical business practices - Mohd Ishan, Zahira; S. M. Hussain, Shaik Mohd Noor Alam (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
This paper examines broadly the doctrine of unconscionability and analyzes to what extent business as well as consumer contracts in Malaysia do not preclude the possibility of unconscionability and unethical bargains. The commercial or business to business contracts look into the relationship in agency and franchising while the consumer contracts specifically relate to the sales of goods, consumer credit as well as sales and purchase of housing. These commercial and consumer contracts are commonly adhesion in nature and are getting more complex in the modern world. This paper would also suggest the statutory requirement of conscionable conduct in all its variation in both the formation as well as performance of commercial and consumer contracts generally. The variation of conscionable conduct refers to conducts that are fair and made in good faith or without undue influence, gross inequality or presumed dishonesty.